Factors Influencing to Choose Social Entrepreneurship as a Career: A Study on Social Entrepreneurship Students from India. (March 2022) - Swain, Sasmita; Patoju, Sri Krishna Sudheer
The present research is designed to evaluate factors influencing the decision of youth in India to choose social entrepreneurship as a career option. A sample of 200 students pursuing a master's in social entrepreneurship was drawn from three Indian universities offering social entrepreneurship courses. Based on literature review and in-depth interview data, 16 measured variables were identified, and a 5-point Likert scale was constructed and validated. The survey data were analysed using the principal component analysis (PCA) method. The final factor structure extracted four (i.e., personal, social, institutional and other) factors. The study concludes that the state needs to create a conducive environment to motivate students to pursue social entrepreneurship as a career option.